2014
DOI: 10.1017/edp.2014.14
|View full text |Cite
|
Sign up to set email alerts
|

Student Wellbeing and the Therapeutic Turn in Education

Abstract: This article considers current concerns with promoting student mental health and wellbeing against the backdrop of critiques of the 'therapeutic turn' in education. It begins by situating accounts of 'therapeutic education' within broader theorisation of therapeutic culture. In doing so, the importance of this work is acknowledged, but key assumptions are questioned. The emergence of concerns about self-esteem and wellbeing are then examined through an analysis of changing educational aims in Australia. This e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 27 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…Drawing on the PNL model (Dormann et al, 2018), loneliness is a negative personal resource confirmed to have deleterious effects on emotions, including mental health and well-being (Diehl et al, 2021;Dinu et al, 2022;Heredia et al, 2017;Kaufmann and Vallade, 2020;Wright, 2014). Since learning engagement is a combination of emotional, cognitive, and behavioral components (Dormann et al, 2018;Fredricks et al, 2004), the relationship between loneliness and engagement becomes relevant.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Drawing on the PNL model (Dormann et al, 2018), loneliness is a negative personal resource confirmed to have deleterious effects on emotions, including mental health and well-being (Diehl et al, 2021;Dinu et al, 2022;Heredia et al, 2017;Kaufmann and Vallade, 2020;Wright, 2014). Since learning engagement is a combination of emotional, cognitive, and behavioral components (Dormann et al, 2018;Fredricks et al, 2004), the relationship between loneliness and engagement becomes relevant.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Interactions created through online channels cannot form effective relational relationships because of the lack of interpersonal connections (Driver, 2018). Loneliness is an effective predictor of mental health and well-being (Diehl et al, 2021;Dinu et al, 2022;Kaufmann and Vallade, 2020;McIntyre-Mills et al, 2018;Wright, 2014), student engagement (Stoliker and Lafreniere, 2015), academic performance (Fan et al, 2021;Singh et al, 2021;Yalçın et al, 2020), lack of sense of community (Reedy, 2019), and dropout intentions (Alkan, 2014). Thus, it is necessary to explore the possible effect of loneliness on student learning experiences (Kaufmann and Vallade, 2020), such as student engagement and academic achievement.…”
mentioning
confidence: 99%
“…Schools are similarly becoming recognised as community providers of mental health support, in what has been termed the 'therapeutic turn' in education. 5 EBIs exist within these settings and have the potential to increase access to mental health guidance and support, particularly for those disadvantaged children and young people who otherwise would not receive help. 6 Yet, despite a widespread call within the field to increase the role of community settings, such as schools and the VCS, in providing support for children and young people, little evidence exists on the capacity and capability of these settings to effectively implement EBIs and adhere to evidence-based practice.…”
Section: The Implementation Of Evidence-based Interventionsmentioning
confidence: 99%
“…You might, for example, be asked to focus very carefully on the sensory experience of eating a raisin or a piece of chocolate, or you might be asked to simply shut your eyes, feel your feet on the ground and bring your attention to your breathing. As you sit through this lesson, you are not only learning about mindfulness, you are also participating in something bigger: the recent so‐called ‘therapeutic turn’ in education (Wright, 2014).…”
Section: Introductionmentioning
confidence: 99%